1998
DOI: 10.1021/cm970312+
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dendrimer Generation on Site Isolation of Core Moieties:  Electrochemical and Fluorescence Quenching Studies with Metalloporphyrin Core Dendrimers

Abstract: The ability of a dendritic shell to afford site isolation to a porphyrin core was evaluated using electron-transfer experiments with a series of porphyrin-core dendrimers. Cyclic voltammograms show that surrounding a porphyrin site with even a small generation (G ∼ 2) dendrimer can significantly lower the rate of interfacial electron transfer, ostensibly by decreasing the proximity of the porphyrin core to the electrode surface. This inhibition of electron transfer is more pronounced when larger generation den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(108 citation statements)
references
References 34 publications
3
102
0
3
Order By: Relevance
“…This type also has one limited hybrid structure and conformation similar to that of the ''type A'' dendrimers. 77,78 The dendritic backbones, which can be compared to branches in a tree, are important for characterization of the dendrimer properties such as electrochemical response [79][80][81][82][83][84][85][86] or photo-reactivity, [87][88][89][90][91][92][93][94][95][96][97] although the backbones do not usually play a central role as the functional center. Modification of the backbones by metal ions should result in drastic changes in the entire conformation, in the environment around the core and in the electronic properties of the dendrimers.…”
Section: Metallo-dendrimer Complexesmentioning
confidence: 99%
“…This type also has one limited hybrid structure and conformation similar to that of the ''type A'' dendrimers. 77,78 The dendritic backbones, which can be compared to branches in a tree, are important for characterization of the dendrimer properties such as electrochemical response [79][80][81][82][83][84][85][86] or photo-reactivity, [87][88][89][90][91][92][93][94][95][96][97] although the backbones do not usually play a central role as the functional center. Modification of the backbones by metal ions should result in drastic changes in the entire conformation, in the environment around the core and in the electronic properties of the dendrimers.…”
Section: Metallo-dendrimer Complexesmentioning
confidence: 99%
“…Other types of phenylazomethine dendrimer (RuG4a, ZnG4b and ZnG4c) were newly synthesized as described in the Supplementary Methods. A benzylether (Fréchet type) dendrimer with a zinc porphyrin core was synthesized as described in the literature 57 . All pyridine derivatives used as guest molecules were purchased or synthesized as described in the Supplementary Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Porphyrins were selected as core molecules because of their potential applications in many areas [156][157][158][159]. Reports dealing with porphyrins decorated with dendrimers had previously appeared [112,[160][161][162][163][164][165][166][167][168]. After investigating three different synthetic strategies for this study, it was concluded that a spacer was required to be attached to the porphyrin to increase the hydrolytic stability and allow synthesis of higher generations.…”
Section: 15mentioning
confidence: 99%